ResearcHER : the power and potential of research careers for women (Emerald Publishing Limited, 2022)
Not all research careers look the same. Not all academics spend their working lives in labs, or dark offices surrounded by dusty books. A research career can mean working in theatres or schools, influencing policy, working with the world's leading brands and businesses, and much, much more. Showing the true diversity of scholarship, and the women leading the way, ResearcHER offers an A-Z of research and researchers from around the world, exploring who researchers are and what they really do, all whilst celebrating female scholarship. Each short chapter offers an insight into a real-life researcher, their background and journey into a research career, what they're currently researching, their top tips for budding researchers, and fun facts and activities to explore yourself. ResearcHER smashes stereotypes to show you that research is not just conducted by men and women in lab coats or stuck in stuffy offices; researchers are women from all backgrounds, researchers come from diverse geographies, are disabled and able-bodied, are transgender, nonbinary, queer. Researchers look just like you, and you could be one too.